MENGEMBANGKAN KOMPETENSI GURU DALAM MENERAPKAN PEMBELAJARAN BERDIFERENSIASI MELALUI KOMUNITAS PRAKTISI - Rodi, Rodi; Sesmiarni, Zulfani; Ismail, Fauzan (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
The purpose of this discussion is the Theory of Islamic Education from the Perspective of the Qur’an and Hadith. The type of research that the writer did was field research which is a qualitative description. Data collection techniques that the authors use are through observation, interviews, and documentation. The validity of the data used is triangulation. From the results of the study indicate that practice in the teacher practitioner community can be in the form of teaching practice and interactions with students or parents. There are 3 differentiations namely: First, content differentiation. The competencies that must be possessed by teachers are pedagogic competence, competence, personality, professional competence, social competence. Second, process differentiation. The strategies carried out by the teacher in differentiating the content to be studied by students are: presenting varied, presenting material with various learning modes, providing various supporting systems. Third, Product Differentiation, the teacher designs what products will be carried out by students in accordance with the , and skills that must be demonstrated by them. The teacher also needs to determine the assessment criteria in the rubric so that students know what will be assessed and what quality is expected from each aspect that they must fulfill.